2011
DOI: 10.1051/0004-6361/201116820
|View full text |Cite
|
Sign up to set email alerts
|

A stringent upper limit to SO2in the Martian atmosphere

Abstract: Surfur-bearing molecules have been found at the surface of Mars by the Viking lander, the Spirit and Opportunity rovers, and the OMEGA infrared spectrometer aboard Mars Express. However, no gaseous sulfur-bearing species have ever been detected in the Martian atmosphere. We search for SO 2 signatures in the thermal spectrum of Mars at 7.4 μm using the Texas Echelon Cross Echelle Spectrograph (TEXES) at the NASA Infrared Telescope Facility (IRTF). Data were obtained on Oct. 12, 2009 (Ls = 353 • ), in the 1350-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 23 publications
3
18
1
Order By: Relevance
“…Similar observations were performed on Mars in October 2009 and led to a stringent upper limit (0.3 ppb) for SO 2 on Mars (Encrenaz et al 2011a). Venus was observed over three nights in 3 spectral ranges, 1350-1358 cm −1 (Jan. 10), 1362-1370 cm −1 (Jan. 11) and 1344-1352 cm −1 (Jan. 12).…”
Section: Observations and Modellingsupporting
confidence: 67%
“…Similar observations were performed on Mars in October 2009 and led to a stringent upper limit (0.3 ppb) for SO 2 on Mars (Encrenaz et al 2011a). Venus was observed over three nights in 3 spectral ranges, 1350-1358 cm −1 (Jan. 10), 1362-1370 cm −1 (Jan. 11) and 1344-1352 cm −1 (Jan. 12).…”
Section: Observations and Modellingsupporting
confidence: 67%
“…No sulfur-bearing species has been detected to date in the Martian atmosphere. Both Encrenaz et al (2011) and Nakagawa et al (2009) reported an upper limit of 2 ppb of SO 2 , while recent groundbased observations of the Tharsis region revealed upper limits of 1.1 ppb . HCl is probably the most abundant reservoir of chlorine on Mars.…”
Section: Expected Performancementioning
confidence: 89%
“…CH 2 O 3× 10 −9 High resolution ground based spectroscopy (Krasnopolsky et al 1997) SO 2 3 × 10 −10 Ground based infrared spectroscopy (Encrenaz et al 2011a(Encrenaz et al , 2011b a δ 13 C VPDB = −2.5 ± 4.3 per mil that was interpreted as an atmospheric contribution from ongoing volcanic outgassing and carbonate formation. Impact erosion is yet another process that could remove an early massive atmosphere (Melosh and Vickery 1989, Owen and Barnun 1995a, 1995b.…”
Section: Atmospheric Compositionmentioning
confidence: 99%
“…Farquhar et al 2000;Greenwood 2000;McCubbin et al 2009), no sulfurous gases have been detected in the martian atmosphere. Recent ground-based spectroscopic observations have placed an upper limit of 0.3 ppb of SO 2 in the current atmosphere (Encrenaz et al 2011a(Encrenaz et al , 2011b. Nevertheless, SAM will search for trace atmospheric constituents such as SO 2 and H 2 S. The SAM QMS is expected to measure the major isotopes of SO 2 evolved from solid samples containing S such as sulfates if these dissociate in the 950-1100…”
Section: Atmospheric Compositionmentioning
confidence: 99%